(untitled) (Eurasian Medical Research Periodical, 2023)
It is one of the weakest segments of the population in terms of quality and quantity indicators of Student Nutrition. In this regard, we conducted a study aimed at identifying the peculiarities of the nutrition of students of Samarkand State Medical University